Ventricular shunt infection strategic issues on the hardest complication of hydrocephalus treatment. - Isabella Nunes Matos; Livia Barros Taumaturgo; Maria Eduarda Quidute Arrais Rocha; Maria Victoria Pessoa Freire; Sarah Ferrer Augusto Gonçalves; Carlos Eduardo Barros Jucá (Brazilian Society for Pediatric Neurosurgery, 2020)
Ventricular shunt (VS) is still the main therapy for hydrocephalus in children. Although many lives can be saved with this procedure, shunts are notoriously prone to complications. Among these, infection is the most difficult to deal with. This paper evaluates most aspects of shunt infection, such as etiology, risk factors, diagnosis, treatment and associated complications. Literature shows that the majority of infections are caused by Staphylococcus, although other microorganisms can be involved, like gram-negatives and Mycoplasma. Etiology is thus variable and medical personel should be aware of it. Due to the potential of VS infection o provoke increasing morbidity and mortality in children, it should be stressed the importance of a correct and fast diagnosis to secure a suitable treatment. Additionally, there isn't an uniform protocol worldwide regarding the use of antibiotics, so it often depends on the physicians suggestion and the preference of the hospital's microbiology team. This situation reinforces the need for frequent update to the most recent literature available.